Pilot study on prevalence of color vision dysfunction in long-term solvent-exposed painters - Ihrig, Andreas; Nasterlack, Michael; Dietz, Michael Christof; Hoffmann, Jörg; Triebig, Gerhard (Industrial health, 2003)
Main purpose of our study was to examine whether painters with long-term exposure to mixtures of organic solvents show slight dysfunctions in color vision ability. The study population consisted of 140 men with chronic exposure to organic solvents from paint and thinners (mean duration of exposure: 26 years). We used the Lanthony Desaturated Panel-D-15 (LDP-D15) to test color vision and calculated the color confusion index (CCI). The results were compared with reference values taken from the literature. Additionally the questionnaire Q18 for solvent related neurotoxic symptoms was applied and its results compared with the CCI. Painters between 25 to 55 years old had higher median CCI values than the respective age group of the references. No statistical significant association between CCI and the actual or chronic solvent exposure was found. The results of the Q18 did also not correlate significantly with the exposure indices. We recommend further studies to explore if the color confusion index is an appropriate indicator of early neurotoxic effects in painters.